Factors Influencing the Shear and Tensile Moduli of Smectic Polydomain Networks. Issue 1 (23rd August 2013) - Yu, Ziniu; Hedden, Ronald C.; Bowman, Christopher N.; Horkay, Ferenc
Summary The molecular and mesoscale factors affecting the shear and tensile moduli of smectic main chain liquid crystal networks (MCLCN) were investigated. Polydomain smectic MCLCN having several different crosslinker concentrations were characterized by dynamic mechanical analysis (DMA) and X‐ray diffraction (XRD) linewidth measurements. The shear and tensile moduli in the smectic state are dominated by the energy cost for deforming smectic layers, while the isotropic shear modulus is governed by the usual entropic cost of deforming elastic network chains.